2015
DOI: 10.1039/c5dt01464f
|View full text |Cite
|
Sign up to set email alerts
|

How to get the desired reduction voltage in a single framework! Metallacarborane as an optimal probe for sequential voltage tuning

Abstract: An appealingly wide set of redox couples ranging from -1.74 to -0.35 V based on a metallabisdicarbollide derivative, [M(C2B9H11-yIy)2](-) (M = Co, Fe), each being distinguished from the former by near 0.15 V and all having the same structure have been demonstrated. The redox active methyl viologen moiety ([MV](2+)) has been used as a benchmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…Redox potentials of complex 3 corresponding to the Fe and Co centers are 0.06 V higher than that of ferrocene[3e] and 0.22 V lower than that of the cobalt bis(dicarbollide) anion, respectively, indicating electron density movement from the iron center in ferrocene to the cobalt metal in cobalt bis(dicarbollide). The Δ V difference of 1.78 V between Co and Fe metal centers is comparable with the 1.74 V difference when measured individually . The absence of two separate signals for the ferrocene units in complex 3 can be interpreted as the absence of communication between the two end groups.…”
Section: Resultssupporting
confidence: 64%
“…Redox potentials of complex 3 corresponding to the Fe and Co centers are 0.06 V higher than that of ferrocene[3e] and 0.22 V lower than that of the cobalt bis(dicarbollide) anion, respectively, indicating electron density movement from the iron center in ferrocene to the cobalt metal in cobalt bis(dicarbollide). The Δ V difference of 1.78 V between Co and Fe metal centers is comparable with the 1.74 V difference when measured individually . The absence of two separate signals for the ferrocene units in complex 3 can be interpreted as the absence of communication between the two end groups.…”
Section: Resultssupporting
confidence: 64%
“…The determined in-plane hexagonal lattice parameter of 0.5 nm fits reasonably well with the 0.6 nm semiaxis length of the cobaltabisdicarbollide groups in a 2D close-packed structure]. 21 Interestingly, in addition to the central hexagon in Figure 16e ascribed to the 2D hexagonal lattice observed in Figure 16d, some extra points are distributed along the FFT diagonal. Far from being an artifact, these points arise from the structural asymmetry of the 7-compound due to the lateral bipyridine unit, which breaks the symmetry plane of the supramolecular packing and appears as the brighter edge of each molecular feature in Figure 16d…”
Section: Self-assembly Propertysupporting
confidence: 71%
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%